Quakers and Abolition - Plank, Geoffrey Gilbert, 1960-; Carey, Brycchan, 1967- (Book collections on Project MUSE., 2014)
"This collection of fifteen insightful essays examines the complexity and diversity of Quaker antislavery attitudes across three centuries, from 1658 to 1890. Contributors from a range of disciplines, nations, and faith backgrounds show how Quakers often disagreed with one another and the larger antislavery movement about slavery itself and the best path to emancipation. Far from having monolithic beliefs, Quakers embraced such diverse approaches as benevolent slave-holding, both gradual and comprehensive abolition, and consumer boycotts of slave-produced products."--Jacket